Les relations publiques au service du changement social - Pascale Caïdor; Alex Blaise; Adama Togola (Communication)
This article focuses on the communication practices of non-profit organizations (NPOs) and aims to deepen understanding of activist public relations practices of organizations in various sectors of activity that face discrimination and are committed to the fight against racial inequality. Activist communication plays a key role in fostering the collective creation of meaning, the formation of support networks and the expansion of movements to combat racial inequality through the dissemination of effective counter-narratives. The main objective of this article is therefore to highlight the public relations practices, tactics and discourse used by organizations involved in the fight against racial inequality. Using a dialogical and co-creative approach, this study seeks to highlight the crucial role of public relations in advocating for and amplifying the voices of marginalized groups by examining the different dimensions of agency that underlie this approach.